PESQUISA E APROVEITAMENTO DE ÁGUA SUBTERRÂNEA PARA ABASTECIMENTO URBANO NAS DUNAS COSTEIRAS DO CEARÁ - Campos, Luiz Alberto Siqueira; Menezes, Maria Amélia Souza (Águas Subterrâneas, 1982)
Resumo não dispoível.